PENGEMBANGAN WINRAH (WEBSITE INTERAKTIF SEJARAH) BERBASIS GOOGLE SITES SEBAGAI INOVASI PADA PEMBELAJARAN IPS SISWA KELAS IV SD - Nurhayati, Annisa; Kusman Rukmana; Nurdinah Hanifah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to Develop a Website-based interactive learning media called WINRAH (Interactive History Website) to support history learning in fourth grade elementary schools. The background of this study is based on the fact that history learning is still dominated by conventional methods and minimal use of digital media that are interesting and relevant to the characteristics of 21st-century students. This study uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). WINRAH media was Developed through the Google Sites platform by integrating various elements such as e-books, podcasts, interactive quizzes, and educational games. The validation results from media experts showed an average score of 96%, while from material experts it was 88%, both of which are classified as very valid. The trial was conducted in three stages: individual (90.88%), small group (89.45%), and large group (88.48%), all of which showed a very good response to WINRAH media. The evaluation also revealed that this media increased learning motivation, material understanding, and active student involvement in learning. Thus, WINRAH media is suitable for use as an alternative history learning media that is innovative, effective, and in accordance with the Independent Curriculum.